Cover Picture: Powering Artificial Enzymatic Cascades with Electrical Energy (Angew. Chem. Int. Ed. 27/2020). Issue 27 (28th April 2020) - Al‐Shameri, Ammar; Petrich, Marie‐Christine; junge Puring, Kai; Apfel, Ulf‐Peter; Nestl, Bettina M.; Lauterbach, Lars
Abstract : Electrical energy powers an artificial enzymatic cascade in a continuous flow reactor. As reported in their Communication on page 10929, L. Lauterbach et al. combined electrolysis in a scalable platform with a H2 ‐ and O2 ‐dependent enzymatic cascade and separated both systems with a gas‐permeable membrane. The synthesis of N‐heterocycles from diamines is demonstrated with up to 99 % product formation along with excellent regioselective labeling with stable isotopes. Cover illustration: Jo Richers.